Looking forward: rethinking professional learning through partnership arrangements in Initial Teacher Education - Edwards, A; Mutton, T (2007)
We draw on evidence gathered from teachers who had responsibility for initial teacher education in their schools as part of training partnership arrangements with universities, in order to examine how they are working within their schools and with their higher education partners. Evidence consisted of questionnaire returns from 60 teachers, interviews with six of these and analyses of partnership documentation. Analyses revealed that many of the schools were working with more than one higher education institution and that some schools were increasingly seeing teacher training as a set of practices which were school-led and which therefore reduced the disruption to schools that may arise in school-based training. With this as a background we then use the lenses of activity theory and findings from two recent studies which have examined boundary crossing in other aspects of schools' work to interrogate the dataset and to consider the implications of multiple partnership arrangements for future developments in the professional learning of both student teachers and teacher-mentors; and links between schools and universities.